The design of Plasma Reactor and Study of Oxgyen Gas Flow Effect against to the Carbon Ashing Rate in Steel K110 - Antonius Prisma Jalu Permana; Bernardus Crisanto Putra Mbulu (Natural B, Journal of Health and Environmental Sciences, 2018)
Thin film technology is a green technology in order to decrease industrial waste. The need of thin film cleaner in recoating process is a must. Build up of a plasma reactor using oxygen gas and generate with 2.45GHz microwave was studied. The main objective of this research was to determine alternative plasma generation using high frequency microwave 2.45GHz as a thin film cleaning media on thin film technology. The results show that plasma could generate with maximum pressure at 3cmHg or 30 Torr and it could decrease carbon on surface of steel K110.